Geographical Patterns of Analysis in IR Research: Representative Cross-Regional Comparison as a Way Forward - Johannes Vüllers (German Institute of Global and Area Studies (GIGA), 2014)
In recent decades, there has been significant debate about the representation of the various world regions in international relations research. This paper contributes to the debate by providing the results of a survey of 290 research articles published over the last decade in three leading disciplinary journals. The survey shows that non-Western cases are indeed underrepresented in the research. However, an analysis of the research articles according to their research topics, objectives, and methodology finds no explanation for this underrepresentation. I argue in this paper that the inclusion of non-Western cases is important to secure the validity of international relations research. "Representative crossregional comparison," which is based on comparative area studies approaches, is presented as a research design that addresses this issue.
Keywords: 300; comparative area studies; non-Western theories; international relations (IR)